Unlocking markets to smallholders: Lessons from South Africa - Schalkwyk, Herman D. van (Mansholt Publication Series, 2011)
This book assesses the institutional, technical and market constraints as well as opportunities for smallholders, notably, emerging farmers in disadvantaged areas such as the former homelands of South Africa. Emerging farmers are previously disadvantaged black people who started or will start their business with the support of special government programs. Public support programs have been developed as part of the Black Economic Empowerment strategy of the South African government. These programs aim to improve the performance of emerging farmers. This requires, first and foremost, upgrading the emerging farmers skills by providing access to knowledge about agricultural and entrepreneurial practices. To become or to remain good farmers they also need access to suitable agricultural land and sufficient water for irrigation and for feeding their cattle. Finally, for emerging farmers to be engaged in viable farming operations, various factors need to be in place such as marketing and service institutions to give credit for agricultural inputs and investments; input markets for farm machinery, farm implements, fertilizers and quality seeds; and accessible output markets for their end products. This book develops a policy framework and potential institutional responses to unlock the relevant markets for smallholders.